Modeling Geoelectric Fields and Geomagnetically Induced Currents Around New Zealand to Explore GIC in the South Island's Electrical Transmission Network. Issue 10 (30th October 2017) - Divett, T.; Ingham, M.; Beggan, C. D.; Richardson, G. S.; Rodger, C. J.; Thomson, A. W. P.; Dalzell, M.
Abstract: Transformers in New Zealand's South Island electrical transmission network have been impacted by geomagnetically induced currents (GIC) during geomagnetic storms. We explore the impact of GIC on this network by developing a thin‐sheet conductance (TSC) model for the region, a geoelectric field model, and a GIC network model. (The TSC is composed of a thin‐sheet conductance map with underlying layered resistivity structure.) Using modeling approaches that have been successfully used in the United Kingdom and Ireland, we applied a thin‐sheet model to calculate the electric field as a function of magnetic field and ground conductance. We developed a TSC model based on magnetotelluric surveys, geology, and bathymetry, modified to account for offshore sediments. Using this representation, the thin sheet model gave good agreement with measured impedance vectors. Driven by a spatially uniform magnetic field variation, the thin‐sheet model results in electric fields dominated by the ocean‐land boundary with effects due to the deep ocean and steep terrain. There is a strong tendency for the electric field to align northwest‐southeast, irrespective of the direction of the magnetic field. Applying this electric field to a GIC network model, we show that modeled GIC are dominated by northwest‐southeast transmission lines rather than east‐west lines usually assumed to dominate. Key Points: We developed a thin‐sheet conductance model, electric field, and GIC network models for New Zealand Strong electric fields on land are aligned perpendicular to New Zealand's main axis for most magnetic field directions Northwest‐southeast transmission lines dominate GIC rather than the expected domination by east‐west lines